(untitled) (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2024)
This research was motivated by a sense of interest in traditions in the area, because the implementation of village clean-ups experienced many changes from the previous year. This is what prompted researchers to conduct research on village clean ceremony traditions. The focus of research on the village clean ceremony tradition is (1) How is the village clean ceremony carried out in Mojokambang Village? (2) What is the purpose of holding a village clean ceremony in Mojokambang Village? (3) What is the community’s view of the village clean ceremony tradition in Mojokambang Village? This research uses a qualitative approach. Data collection procedures use observation guidelines, interviews, documentation, literature review. The village cleaning ceremony itself is carried out once a year during the first harvest on Friday Pahing. The village cleansing ceremony is carried out by bringing the tumpeng/ambeng to the punden which is followed by the village community and a kenduri is held which will be led by the punden caretaker to convey wishes and recite prayers. In this case, the author hopes that the village community will continue to carry out this tradition to preserve the traditions that have existed for a long time